'Happiness' from a sociological view: the case of Çokal Dam. (2015) - Kop, Zeynep Buyan; Kasapoglu, Aytul
The Çokal Dam project is a large government development that aims to provide both drinking and irrigation water to the entire Gallipoli Peninsula in Turkey. Despite its obvious benefits, certain communities have been and are currently negatively impacted by the project. Similar projects have been implemented in Turkey with enormous negative effects on local communities. This study explores the impact of the effects of land loss, on one hand and a continuous water supply, on the other hand, on happiness and well-being. The variables that affect happiness and well-being are also examined while examining the effects of the project. As a result, it is reasonable to conclude that the Çokal project's positive and negative effects cancel one another out and that the Çokal villagers' attitudes and statements of happiness regarding the project have been much more positive than expected. This study also emphasises that attitudes toward large developments can be positively transformed when 'social impact assessment' processes are applied effectively.